Maxillaria purpureo-nigra (Orchidaceae: Maxillariinae), a new species from Southwestern Ecuador belonging to Maxillaria sect. Rufescens - Romero, Bosco Javier Zambrano; Carnevali, Germán; Solano, Rodolfo (Phytotaxa, 2020)
Maxillaria purpureo-nigra Zambrano, Carnevali & Solano, a new species recently collected in Southwestern Ecuador is described and illustrated. Information concerning its distribution, habitat, phenology, and conservation status is provided. The new taxon is a member of Maxillaria sect. Rufescens, and it is compared with morphologically similar species such as M. culebrica, M. dressleriana, M. hedwigiae, and M. richii. However, we consider that it is more similar to M. prunina, from which it differs by its deep purple flowers, with oblong-elliptic sepals, oblong-lanceolate petals with acute apex, and a lip with an oblong-ovate mid-lobe suffused with dark-purple at the center, including the callus. We also provide a key to the Ecuadorean species of M. sect. Rufescens.